2008
DOI: 10.1038/sj.ejhg.5201973
|View full text |Cite
|
Sign up to set email alerts
|

The I105V polymorphism in glutathione S-transferase P1, parental smoking and the risk for nonsyndromic cleft lip with or without cleft palate

Abstract: Genetic variations in the detoxification enzyme glutathione S-transferase P1 (GSTP1) may modify the teratogenicity of lifestyles, such as smoking. We investigated the role of the I105V polymorphism in GSTP1, parental periconception smoking, and their interaction with nonsyndromic cleft lip with or without cleft palate (CL/P) risk in the offspring. The GSTP1 I105V polymorphisms were determined in Dutch nonconsanguineous Caucasians comprising of 155 CL/P triads (mother, father, child) and 195 control triads. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is interesting to note effects of maternal genotype and maternalspecific environmental modifiers such as smoking, drinking and vitamin intake during pregnancy on oral cleft susceptibility have been previously reported in various studies. 2,[10][11][12][13][14][15][16][17][18][19] However, it should be noted that the parental asymmetry tests we applied here do not specifically test for maternal effects which would be expected to occur via alterations of the in utero environment. Calculation of genomic inflation factors for the MAT and PAT tests showed a small increase for the MAT compared with the PAT in all categories, this increased inflation factor in the MAT does not discern the underlying cause, being consistent with either a true excess of biological associations with the maternally inherited alleles, or alternatively differing population structure between the two parental populations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, environmental studies have indicated maternal smoking, and potentially alcohol consumption, during pregnancy greatly increase the risk of clefting in offspring, with some evidence of genetic interactions. 2,10,11 Similarly, according to several studies, multi-vitamin supplements with or without folic acid taken during pregnancy have been shown to decrease the risk of oral clefting, with a stronger effect seen in CL/P as compared with CPO. [12][13][14] If levels of circulating folate are influenced by genetic factors, then it can be hypothesized any maternal genes involved in dictating circulating folate levels could also alter the risk of OFCs in the fetus.…”
Section: Introductionmentioning
confidence: 97%
“…25 Meanwhile, polymorphisms of several genes, including MSX1, TGFB3, BCL3, CYP1A1, GSTP1, and GSTT1 have been examined in conjunction with maternal alcohol consumption, cigarette smoking, medication use, and multivitamin supplementation during pregnancy. [25][26][27] It was shown that smoking by both parents interacts with a specific allelic variant of MSX1, which significantly increase the OFC risk for their offspring. 28 Moreover, a novel approach was developed by Wehby et al 26 to study the role of maternal smoking and OFC, in which they found out that smoking before and during pregnancy increased the risk of OFC by about 4-5 times at the sample average smoking rate.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that were studied were mainly folic acid and vitamin supplements, smoking, and maternal passive smoking. Furthermore, only a small number of gene variants were analyzed [25][26][27][28]. In our study, we focused on the interaction between environmental factors and maternal genes to assess any direct maternal effect occurring during pregnancy.…”
Section: Gene Environment Interactionmentioning
confidence: 99%